1996
DOI: 10.1007/bf00052506
|View full text |Cite
|
Sign up to set email alerts
|

Emerging concepts: Angiotensin-converting enzyme inhibition in coronary artery disease

Abstract: Angiotensin-converting enzyme (ACE) inhibitors have played a highly beneficial role in the therapy of hypertension and congestive heart failure. Detailed analysis of some of the heart failure trials in patients with these diseases has uncovered unexpected benefits in the prevention of cardiovascular events. Paralleling these observations are the rapidly accruing basic studies describing important molecular and cellular effects of these agents. For example, ACE inhibition will prevent stimulation of smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…111 ACE inhibitors appear to have anti-atherosclerotic effects as well. 114 ACE inhibitors 114,115 and ARBs 116 may reverse endothelial dysfunction in atherosclerotic animals. It has been suggested that these effects may be similar in humans.…”
Section: End-organ Potential Protection Of Arbsmentioning
confidence: 99%
See 1 more Smart Citation
“…111 ACE inhibitors appear to have anti-atherosclerotic effects as well. 114 ACE inhibitors 114,115 and ARBs 116 may reverse endothelial dysfunction in atherosclerotic animals. It has been suggested that these effects may be similar in humans.…”
Section: End-organ Potential Protection Of Arbsmentioning
confidence: 99%
“…144,145 The best predictor of the value of the ARBs is the usefulness already seen with the ACE inhibitors in the prevention and treatment of congestive heart failure and the improvement of endothelial function. [114][115][116][117] Drugs that interrupt the reninangiotensin system have been shown in animal and human studies to exert renoprotective effects as well as favorable hemodynamic and neurohormonal effects when tested in human heart failure. 146,147 It has been postulated that some of the beneficial effects seen with the ACE inhibitors are due to increased bradykinin levels.…”
Section: Future Development and Indicationsmentioning
confidence: 99%
“…The favourable effects of ACE inhibitors seem to be related to their ability to release local vasodilators such as nitric oxide (NO) as well as to antagonize the vasoconstrictive effects of angiotensin II [32]. In addition, ACE inhibitors can counteract several atherosclerotic processes, including proliferation of vascular smooth muscle cells, low-density lipoprotein (LDL) oxidation, local accumulation of neutrophils and thrombosis [33]. The increase in tissue levels of ACE inhibitor, determined by concomitant administration of HCTZ, could contribute to the development of organ-protective effects of ACE inhibitor therapy; therefore, an highly lipophilic ACE inhibitor, such as zofenopril, would take advantage of co-administration with HCTZ, in comparison to an hydrophilic ACE inhibitor, such as lisinopril [11].…”
Section: Peculiar Characteristics Of the Fixed Combination Zofenoprilmentioning
confidence: 99%
“…In addition, transgenic mice, including increasing the migration of monocytes and their adhesion to endothelial cells at sites of vascular injury carrying both the human renin and angiotensinogen genes, develop accelerated atherosclerotic changes limited [96], promoting the release of tumor necrosis factorfrom monocytes [96], increasing levels of plasminogen to the aortic root when fed a high cholesterol diet [91]. Moreover, in monkeys fed a high cholesterol diet, there activator-1 (PAI-1) via its antagonism of tissue plasminogen activator [94,97], and by raising levels of endothelin is an approximate 3-fold elevation of chymase RNA in areas of the aorta involved with atherosclerotic plaque [94]. ACE inhibitors can lower endothelin levels [98].…”
Section: Changes In Cardiac Angiotensin II and Angiotensin Receptors mentioning
confidence: 99%